(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the linguodidactic essence of the concept of bilingual competence, its structural components, and the peculiarities of its formation. It also provides a scientific substantiation of the role and significance of the CLIL (Content and Language Integrated Learning) approach in the development of this competence. The possibilities for developing students’ communicative and cognitive competences through the integration of language and subject content based on the CLIL approach are highlighted.